2012
DOI: 10.1007/s12105-012-0332-0
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Sinus Osteoma with Osteoblastoma-like Histology and Associated Intracranial Pneumatocele

Abstract: Osteomas of the cranial sinuses are rare, benign bony tumors that can be complicated by the formation of an intracranial pneumatocele. If not treated promptly, a pneumatocele can lead to abscess formation, meningitis, or ventriculitis. In the present case, an intracerebral pneumatocele was formed when an 18 cm 3 osteoma breached the posterior wall of the frontal sinus creating a one-way valve through which air could enter the intracranial cavity. The patient presented after forceful sneezing with nonspecific s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…[10] In the current case, the patient had suffered from headaches, retro-orbital pain and nasal obstruction for a year. Paranasal CT findings showed the osteoblastoma, so endoscopic sinus surgery was applied to the patient.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…[10] In the current case, the patient had suffered from headaches, retro-orbital pain and nasal obstruction for a year. Paranasal CT findings showed the osteoblastoma, so endoscopic sinus surgery was applied to the patient.…”
Section: Discussionmentioning
confidence: 78%
“…[8] Osteoblastomas are usually wellcircumscribed masses. [9,10] The tumor usually shows radiolucent deficits with varying degrees of calcification.…”
Section: Discussionmentioning
confidence: 99%
“…Very rarely, sinonasal osteomas arise as a component of Gardner syndrome and in the current case the patient was otherwise healthy and did not manifest any features of the syndrome [4,5]. Clinically sino-orbital osteomas can present with a broad spectrum of signs and symptoms that may include pain, headache, facial distortion, proptosis, polyps, rhinorrhea, epistaxis, periorbital edema and visual changes; true mucoceles and infections may result when frontal sinus osteomas cause nasofrontal duct obstruction, whereas pneumatocele, cerebrospinal fluid leakage, meningitis and cerebral abscess can occur from tumors that erode the supraorbital plate and dura mater [4,6,7]. These symptoms are due to mass effect and it has been suggested that osteomas remain asymptomatic until they reach a certain size [8].…”
Section: Discussionmentioning
confidence: 99%
“…Microscopically, ossifying fibromas and fibrous dysplasia, are readily separated based on the usual presence of abundant collagenous fibroblastic tissue. The presence of mild cytologic atypia in the large osteoblasts rimming thin trabeculae of osteoid may result in consideration of an osteoblastic osteosarcoma, however evidence of maturation and an absence of atypical stromal cells precludes a diagnosis of osteosarcoma [7]. Ultimately, distinguishing osteoma with osteoblastoma-like features from these entities requires correlating both morphologic and radiographic findings.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the operation, almost all intraocular complications were successfully eliminated. Histological examination of the material removed from the sinus confirmed the presence of a compact osteoma and chronically inflamed FROM PRACTICE Это доброкачественное костное образование неизменно вызывает интерес у практических оториноларингологов, ему посвящено большое количество публикаций, охватывающих различные стороны этой патологии [3][4][5][6][7][8].…”
unclassified